PLAN FOR PREVENTION AND IMPROVEMENT OF THE QUALITY OF URBAN SLUMS IN BALANGAN REGENCY, SOUTH KALIMANTAN PROVINCE, INDONESIA - Wicaksono, Rino (International Journal of Social Service and Research, 2024)
The purpose of this study is to design a comprehensive plan to prevent and improve the quality of urban slums in Balangan Regency, South Kalimantan Province. The research utilizes both literature study and field observation to gather data. The literature study involves analyzing existing urban planning documents, government reports on housing and urban development, statistical data from local and national statistics bureaus, and academic studies related to urban settlements and their improvement. The field observation complements the literature study by providing primary data through direct engagement with the city/district governments, offering a foundational basis for further investigation. The qualitative analysis of these observations, combined with thematic analysis of interview and survey responses, allows for an in-depth understanding of the current challenges and potential solutions. The RP2KPKP document contains the background of the preparation of the RP3KP, the purpose of the planning, the review of policies related to settlements in Pandeglang Regency and the profile of settlements along with the identification of slack areas and their handling needs. Based on these findings, it was concluded that Balangans Regency has a plan to reduce the number and quality of the population of the region. The implementation of this plan is expected to have a positive impact on improving the condition of a community and improving the welfare of the people of the area as a whole. The plan has been formulated with an approach that includes active community supervision, control, and empowerment.